Women Ulema's Perceptions of Efforts to Resolve Patriarchal Hegemony in Pesantren - Prastiwi, Dera Emilia; Farihah, Irzum (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Students with all the activities they undertake, have responsibility for their environment, because they both have complementary responsibilities. Various activities that require order from the students, of course, must be done together without exception looking at gender (men and women have the same position), but the reality that occurs is that patriarchal culture often corners women (santriwati) as objects of gender injustice. This article aims to see how the perception of Women Ulema towards efforts to resolve patriarchal hegemony in Islamic boarding schools. The data was obtained through interviews with Female Ulama, namely Nyai, who also plays a role in the academic field. The results of this research found several efforts to resolve patriarchal hegemony in Islamic boarding schools, namely by improving the learning system in Islamic boarding schools, training leadership, conducting conservative education, reframing the understanding of religious doctrines that are not women-friendly and fair in dividing tasks between male and female students and prioritizing human values (humanization). So this research is very interesting and becomes a new study because it focuses on solving women's resistance efforts that have not been able to tear down patriarchal fortresses.